A qualitative investigation of imagery use and meta-imagery processes among elite canoe-slalom competitors - MacIntyre, T. E.; Moran, A. P. (Journal of Imagery Research in Sport and Physical Activity, 2007)
Imagery research has accumulated in two main waves since it was first investigated over a century ago. Firstly, in a period roughly extending over a century from the 1890s to the 1990s, several hundred experiments focused on the efficacy of the "mental practice" effect. More recently, attempts to shed light on the precise tasks or functions for which athletes use visualization in actual sport situations have led to an upsurge in imagery research. Central to this second wave of research is the imagery use framework (Hall et al., 1998), which has led to over 20 studies. Unfortunately, despite making significant advances these studies have a number of limitations, including a failure to include elite participants and the fact that they have largely overlooked meta-imagery abilities of the athletes. To address these issues, semi-structured interviews were used to explore imagery experiences among elite athletes. Canoe-slalom, which had been subject to previous research on imagery (e.g., White & Hardy, 1998), was the chosen sport. Five female and seven male elite level competitors (age= 25 years; SD = 4.16) participated. Findings from the elite athlete sample were inconsistent with previous research with regard to the motivational function of images. Furthermore, the athletes demonstrated a sophisticated understanding of imagery processes including imagery of realistic behaviours rather than perfect performance. Interestingly, the frequency of debilitative imagery was surprising given previous findings but may have been a consequence of the qualitative methods employed. Finally, examination of the meta-imagery construct proved valuable and is worthy of further research.